2023
DOI: 10.1088/1361-6501/acce58
|View full text |Cite
|
Sign up to set email alerts
|

Online evaluation of resistance spot welding quality and defect classification

Abstract: Resistance Spot Welding (RSW) is widely used in industrial product manufacturing, and weld quality is critical to ensuring the safety and reliability of mechanical structures. In order to improve the product quality, online monitoring of weld quality has become a priority. Therefore, a method based on online evaluation of mild steel RSW quality and automatic defect classification is proposed. First of all, the optimal welding parameters for DC01 mild steel RSW are determined, and the welding parameters are sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…On the other hand, for [56,61], as the monitoring setup includes pressure sensors, the feasibility may be limited to stationary applications, but this depends on the design of the welding machine. The majority of the available studies for expulsion's online assessment [81][82][83][84] based their success on the classification of features extracted from the dynamic signals of the current, voltage, and pressure. Finally, another aspect that makes online expulsion assurance a real thing is the available studies concerning cases that involve different materials and welding infrastructure.…”
Section: A Realistic Scenario For Online Quality Assessment In Produc...mentioning
confidence: 99%
“…On the other hand, for [56,61], as the monitoring setup includes pressure sensors, the feasibility may be limited to stationary applications, but this depends on the design of the welding machine. The majority of the available studies for expulsion's online assessment [81][82][83][84] based their success on the classification of features extracted from the dynamic signals of the current, voltage, and pressure. Finally, another aspect that makes online expulsion assurance a real thing is the available studies concerning cases that involve different materials and welding infrastructure.…”
Section: A Realistic Scenario For Online Quality Assessment In Produc...mentioning
confidence: 99%
“…Research has found that certain signals released in the welding process are strongly correlated with the formation and development of nugget, such as electrode displacement signal, electrode pressure signal, acoustic emission signal, and dynamic resistance signal [16][17][18][19][20]. Zhang et al [21] divided the welding process into three stages, explained the relationship between dynamic resistance and welding quality, and held that welding quality is related to the extreme value of dynamic resistance.…”
Section: Introductionmentioning
confidence: 99%